Effect of commercially available probiotic product on the level of salivary microflora in children of West Bengal - Barun Dasgupta; Shabnam Zahir (Wolters Kluwer Medknow Publications, 2014)
Context: Newer concepts and methods are being researched and being implemented every day. One such newest variety of preventive measure is the use of probiotics. Aims: This study tries to explore the effect of commercially available probiotic product on the level of the salivary microflora in children of West Bengal in a specific period. Materials and Methods: The study was of a randomized, placebo-controlled design. The total of 90 children between age group 6 and 14 years were selected at random, as study and control group. The study group was provided with the commercially available probiotic product "Eugi" sachet with milk as a vehicle for "21" days, whereas control group is provided with only plain milk. Salivary concentration of few specific cariogenic bacteria was measured in both study and control group in the beginning and at the interval at 0, 1, 3, and 5 months. Statistical Analysis Used: Average, standard deviation for a varied comparison was calculated. Student's t-test and probability test were performed. Results: The significant difference in between control and study group only existed at 1-month interval and difference again became insignificant in respective intervals ahead. Conclusions: The study concluded that, (1) there was significant reduction of Gram-positive colony (GPC) counts after 1 month in the probiotic consumed group. (2) During the interval of 1 to 3 months, the GPC counts showed increase in a number and they were restored to the baseline concentration which was maintained till the 5 th month. (3) There was no significant variation in GPC count between different age groups at all intervals.